Endodormancy Release Can Be Modulated by the GA4-GID1c-DELLA2 Module in Peach Leaf Buds - Li, Sen; Wang, Qingjie; Wen, Binbin; Zhang, Rui; Jing, Xiuli; Xiao, Wei; Chen, Xiude; Tan, Qiuping; Li, Ling (Frontiers in Plant Science, 2021)
Gibberellin (GA) plays a key role in the release of bud dormancy and the GA receptor GID1 (GIBBERELL ININSENSITIVE DWARF1) and DELLA protein are the GA signaling parts, but the molecular mechanism of GA-GID1-DEllA module regulating leaf bud dormancy in peach (Prunus persica) is still not very clear. In this study, we isolated and characterized GA INSENSITIVE DWARF1 gene PpGID1c from the peach cultivar ‘Zhong you No.4’. Overexpressing PpGID1c in Arabidopsis promoted seeds germination, which indicated that PpGID1c have an important function in dormancy. The expression level of PpGID1c in peach leaf buds during endodormancy release is higher than that during ecodormancy, and is positively correlated with GA4 levels. Our study also found that GA4 had the most obvious effect on promoting the bud break, indicating GA4 may be the key gibberellin to promote the peach leaf bud endodormancy release. Moreover, qRT-PCR found GA4 can increased the expression of the Gibberellin signaling genes PpDELLA2. A yeast two-hybrid (Y2H) assay suggest PpGID1c interaction with the PpDELLA1 protein was not dependent on Gibberellin, while PpGID1c interaction with PpDELLA2 required GA4 or other Gibberellin. These findings suggest that GA4-GID1c-DELLA2 module regulate peach leaf bud endodormancy release, and significantly enhance our comprehensive understanding the bud endodormancy release and revealing a new mechanism for regulating leaf bud endodormancy release in peach.